Penambahan Tepung Rimpang Temulawak (Curcuma xanthorriza Roxb) dan Tepung Rimpang Temu Putih (Curcuma zedoaria Rosc) dalam Ransum Komersial Terhadap persentase Karkas, Lemak Abdomen, Dan Persentase Hati Pada Ayam Pedaging. - Golla, yustin; Montong, M E.R; Laihad, Jacqueline T; Rembet, Godlief D.G (Universitas Sam Ratulangi, 2014)
This research aims to determine the extent which the effectiveness of the addition of turmeric powder (Curcuma Roxb xhantorriza) and a ginger and white (Curcuma zedoria Rosc) in commercial rations on carcass percentage, amdominal fat, and the percentage ol liver in bloiler. The material used is old broiler 3 weeks as much as 53 tails. The design used was a completely randomized design with 6 treatments 3 replications. The treatmens were applied as follows: R0 = basic ration without ginger, and ginger and white, R1 = base + 2% ration ginger rhizome flour, R2 = base + 2% ration rhizome ginger and white flour. The result sho wed that the edition of flour and ginger rhizome of ginger and white flour in the ration was not significantly different (p > 0,05) on carcass percentage, abdominal fat, liver percentage. It can be concluded that the addition of ginger rhizome flour and white flour as much as 2% in the commercial ration still give the same response to the carcass percentage, abdominal, and the percentage of liver. Keywords : Broiler Chicken, Ginger Rhizome Flour, Ginger And White